2022
DOI: 10.1002/jez.2654
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of salinity and ammonia on the growth behavior, stress‐related markers, and hepato‐renal function of common carp (Cyprinus carpio)

Abstract: One of the most critical factors affecting aquaculture efficiency is the capability of releasing ammonia from the water. By applying a high salinity strategy, this study provides a prompt approach for removing high ammonia levels and relieving its adverse impacts on common carp. The study investigated five groups with triplicates | © 2022 Wiley Periodicals LLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Cortisol and glucose levels serve as common indicators of stress in fish [ 75 , 76 ]. An increase in cortisol and ammonia levels has been documented in previous research in response to individual exposure to ammonia stress [ 12 , 77 , 78 ] or Shewanella infection [ 33 ]. By examining cortisol and glucose levels; we can better understand the interplay between stress response, Shewanella spp.…”
Section: Discussionmentioning
confidence: 83%
“…Cortisol and glucose levels serve as common indicators of stress in fish [ 75 , 76 ]. An increase in cortisol and ammonia levels has been documented in previous research in response to individual exposure to ammonia stress [ 12 , 77 , 78 ] or Shewanella infection [ 33 ]. By examining cortisol and glucose levels; we can better understand the interplay between stress response, Shewanella spp.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that the decreasing salinity level at 20 °C can increase the ionization of NH 3 − by 9% (Khoo et al 1977 ; Kır et al 2019 ; Sinha et al 2015 ). Hence, the ammonia effects are more toxic in the case of low salinity levels, which has been confirmed in common carp ( Cyprinus carpio ) (Dawood and Sewilam 2023 ), European sea bass ( Dicentrarchus labrax ) (Kır et al 2019 ), and Pacific white shrimp ( Litopenaeus vannamei ) (Long et al 2021 ).…”
Section: Introductionmentioning
confidence: 90%
“…African catfish showed optimal FCR and growth rates when reared in FW and signs of increased energy allocation for maintaining normal function and metabolism, such as elevation of plasma cortisol and oxidative stress, were seen with increasing salinity 115 . Grass carp and common carp grew fastest with the lowest FCR at 0 and 2‰, compared with slightly higher salinities 91,264 . Tambaqui, another stenohaline FW species, grew fastest at 0‰ with no difference in FCR observed between 0 and 10‰, 118 while the Nile tilapia, naturally occurring in FW and tolerant of BW, grew the fastest between 0 and 8‰, with optimal FCR at 8‰ at 32°C 265 .…”
Section: Implications For Productionmentioning
confidence: 97%
“…115 Grass carp and common carp grew fastest with the lowest FCR at 0 and 2‰, compared with slightly higher salinities. 91,264 Tambaqui, another stenohaline FW species, grew fastest at 0‰ with no difference in FCR observed between 0 and 10‰, 118 while the Nile tilapia, naturally occurring in FW and tolerant of BW, grew the fastest between 0 and 8‰, with optimal FCR at 8‰ at 32 C. 265 Compared with FW fish, euryhaline species generally exhibit optimal growth rates at intermediate salinities. Goldlined seabream (Rhabdosargus sarba) showed the highest growth rate and protein efficiency ratios at 15‰ relative to other salinities.…”
Section: Growth and Feed Utilisationmentioning
confidence: 98%